Intraductal tubulopapillary neoplasm with expansile invasive carcinoma of the pancreas diagnosed by endoscopic ultrasonography‐guided fine needle aspiration: A case report. Issue 4 (14th December 2013) - Furuhata, Ayako; Minamiguchi, Sachiko; Mikami, Yoshiki; Kodama, Yuzo; Sumiyoshi, Shinji; Adachi, Souichi; Haga, Hironori
<x xml:space="preserve">Abstract</x> Intraductal tubulopapillary neoplasm (ITPN) of the pancreas, a novel entity included in the World Health Organization 2010 classification, accounts for <1% of all pancreatic exocrine neoplasms and the number of reported cases is limited in the English literature. Herein we describe the cytologic features of ITPN with invasive carcinoma showing expansile growth on endoscopic ultrasonography‐guided fine needle aspiration (EUS‐FNA) cytology. A 74‐year‐old male patient is presented with a 6.2 cm irregular mass in the head of the pancreas. Microscopic examination of EUS‐FNA material showed abundant branching clusters of cells, with some scattered discohesive cells. High power magnification revealed tubular and cribriform patterns with central lumina, containing mucinous or proteinaceous secretions. The constituent cells were relatively uniform and showed mild to intermediate nuclear atypia. Intracytoplasmic mucin was not identified. On cell‐block preparation, luminal spaces of clusters contained wispy luminal mucin. Immunohistochemically, constituent cells were positive for MUC1 and MUC6, and were negative for MUC5AC. The large cribriform and tubular clusters with luminal spaces containing wispy mucin were considered to be diagnostic clues for the cytologic diagnosis of ITPN by EUS‐FNA. MUC1, MUC6, and MUC5AC immunohistochemistry for cell‐block preparation appears to be a useful adjunctive tool to confirm the diagnosis. On EUS‐FNA, ITPN should be included in the differential diagnosis of a pancreatic mass lesion showing good circumscription. Diagn. Cytopathol. 2014;42:314–320. © 2013 Wiley Periodicals, Inc.